DYNAMICS OF STRUCTURAL AND FUNCTIONAL STATUS OF MYOCARDIUM DUE TO COMBINATION THERAPY WITH AMLODIPINE AND BISOPROLOL IN PATIENTS WITH ARTERIAL HYPERTENSION - I. L. Zapesochnaya; A. G. Avtandilov (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the effect of 6-month therapy with combination of amlodipine and bisoprolol on the structural and functional status of the myocardium in hypertensive patients who work in the Far North.Material and methods. 140 hypertensive patients who live in the Khanty-Mansiysk Autonomous District - Yugra were divided into two groups depending on arrangement of working time. The first group included 72 patients who work only day shift; the second group – 68 patients who work alternate (day/night) shifts. Combination therapy with amlodipine and bisoprolol assigned to all patients. Echocardiography was performed at baseline, after 12 weeks, and after 6 months of therapy.Results. The target blood pressure (BP) level in group 1 was achieved in 92.9%. A share of patients with normal left ventricular (LV) geometry increased from 37.5 to 44.8%; a share of patients with concentric and eccentric LV hypertrophy (LVH) decreased from 30.6 to 23.9% and 19.4 to 19.2%, respectively. Target BP level in group 2 was achieved in 87.9%. A share of patients with normal LV geometry increased from 23.5 to 33.3%; while share of patients with concentric and eccentric LVH decreased from 45.6 to 38.1% and from 19.1 to 17.4%, respectively. A positive correlation between LV myocardial index and average daily systolic and diastolic BP was found.Conclusion. Revealed changes in BP and in LV structure and function due to treatment with amlodipine and bisoprolol can be considered as cardioprotective effect of this combination in hypertensive patients who work in the Far North. This effect was more pronounced in hypertensive patients working alternate (day/night) shifts.